Digital Learning Quality: Bring Your Own Device (BYOD) and 4C Skills at Higher Education - Mu'alimin, Mu'alimin; Sutomo, Moh. (AT-TA'LIM, 2023)
The digital era has an impact on education and the quality of learning. Digital devices are a necessity in classroom learning. Bringing equipment to class for learning is still considered 'unnatural' for educators and educational institutions. On the other hand, the device can be used as a medium to find materials in classroom learning. The purpose of this study is to examine the quality management of learning in higher education by bringing their own tools (BYOD) to classroom learning to improve 21st century skills in the Islamic Education Management study program at UIN KHAS Jember. This research is qualitative research, using observations, interviews and documentation as data collection and interactive data analysis. This research used 45 students as informants. The results showed that the personal devices used by students in classroom learning brought benefits to critical, creative, collaborative, and communicative thinking skills. The benefits of using BYOD in the classroom are motivating and improving student participation in class discussions.